Rice Stress Associated Protein 1 (OsSAP1) Interacts with Aminotransferase (OsAMTR1) and Pathogenesis-Related 1a Protein (OsSCP) and Regulates Abiotic Stress Responses - Kothari, Kamakshi S.; Dansana, Prasant K.; Giri, Jitender; Tyagi, Akhilesh K. (Frontiers in Plant Science, 2016)
Stress associated proteins (SAPs) are the A20/AN1 zinc-finger containing proteins which can regulate the stress signaling in plants. The rice SAP protein, OsSAP1 has been shown to confer abiotic stress tolerance to plants, when overexpressed, by modulating the expression of endogenous stress-related genes. To further understand the mechanism of OsSAP1-mediated stress signaling, OsSAP1 interacting proteins were identified using yeast two-hybrid analysis. Two novel proteins, aminotransferase (OsAMTR1) and a SCP/TAPS or pathogenesis-related 1 class of protein (OsSCP) were found to interact with OsSAP1. The genes encoding OsAMTR1 and OsSCP were stress-responsive and showed higher expression upon abiotic stress treatments. The role of OsAMTR1 and OsSCP under stress was analyzed by overexpressing them constitutively in Arabidopsis and responses of transgenic plants were assessed under salt and water-deficit stress. The OsAMTR1 and OsSCP overexpressing plants showed higher seed germination, root growth and fresh weight than wild-type plants under stress conditions. Overexpression of OsAMTR1 and OsSCP affected the expression of many known stress-responsive genes which were not affected by the overexpression of OsSAP1. Moreover, the transcript levels of OsSCP and OsAMTR1 were also unaffected by the overexpression of OsSAP1. Hence, it was concluded that OsSAP1 regulates the stress responsive signaling by interacting with these proteins which further regulate the downstream stress responsive gene expression.